Determinants of Interest Rate Spread of Nepalese Commercial Banks - Shrestha, Purna Man (Journal of Business and Social Sciences Research, 2022)
This paper has analysed the determinants of interest rate spread (IRS) of Nepalese commercial banks. The panel data of 25 commercial banks from 2013/14 to 2020/21 was used for the analysis. The study used return on assets (ROA), management efficiency (ME), capital adequacy ratio (CAR), assets quality (AQ), and credit risk (CR, and operational efficiency (OE) as the bank specific determinants and inflation (INF) and growth rate of gross domestic product (GDP) as the macroeconomic determinants. Using the random effect model, the paper finds ROA, CR, ME, and OE as the major bank specific determinants and INF and GDP as the major macroeconomic determinants of interest rate spread. Similarly, the role of ROA, CR, INF and GDP was found to be positive while that of ME and OE was discovered as a negative role in determining IRS of Nepalese commercial banks. The findings of this study can be useful in formulating policies on the spread rate of interest.